The psychological impact and experience of breast cancer screening in young women with an increased risk of breast cancer due to neurofibromatosis type 1 - Crook, Ashley (Fam Cancer, 2021)
Women with neurofibromatosis type 1 (NF1) have an increased risk of developing early breast cancer with a poorer prognosis compared to the general population. Therefore, international management guidelines recommend regular screening in women with NF1 starting from 30 to 35 years. As the psychological impacts of breast cancer screening in other high-risk populations cannot be extended to women with NF1, due to increased incidence of cognitive and mental health issues, the psychological harms of breast screening in women with NF1 are unknown. Consequently, the aim of this study was to assess the psychological impact of breast cancer screening in women with NF1 attending an established risk management clinic. Twenty-eight women with NF1 (30–50 years) completed psychological well-being and patient experience questionnaires, administered across five time points, before and after their initial and second round annual breast screening visits. Preliminary findings demonstrated the screening regimen was well-tolerated, with most participants reporting high satisfaction with the screening process. Overall, no significant increase in psychological distress related to the breast screening process was identified, with mean cancer worry and anxiety scores decreasing over time. However, some women did experience negative aspects of screening and barriers to re-attendance at annual breast screening appointments. As some women with NF1 exhibited clinical levels of psychological distress prior to screening, efforts to identify those at risk and additional support to address concerns and expectations throughout the breast screening process may be beneficial. SUPPLEMENTARY INFORMATION: The online version contains supplementary material available at 10.1007/s10689-021-00259-9.